Internal Auditors’ Role in Shaping the Effectiveness of Internal Control System in Manufacturing Companies - Rastina, Rastina; Ratnawati, Ratnawati; Astanty, Wamika Febri; Idrus, Muhammad Ishlah (International Journal of Social Science and Business, 2025)
The Internal Control System (ICS) is a fundamental mechanism for ensuring operational effectiveness, regulatory compliance, and the reliability of financial reporting, particularly within manufacturing companies that face complex production processes and heightened risk exposure. This study analyzes internal auditors’ perceptions of ICS effectiveness in the manufacturing sector, focusing on five critical factors: the gap between formal ICS design and practical implementation, the extent of top management support, auditor independence, auditors’ competence in technology-based systems such as ERP, and the organizational culture toward auditing. A descriptive qualitative method was employed, combining semi-structured, in-depth interviews with seven internal auditors from three medium- and large-scale manufacturing companies, supplemented by documentation review. The sample was deliberately chosen because medium- and large-scale firms typically operate with more complex internal controls and higher exposure to financial and operational risks, making them particularly relevant for assessing ICS effectiveness. The number of interviews (seven) was deemed appropriate to achieve thematic saturation while still allowing for in-depth exploration of auditors’ individual experiences. Data were thematically analyzed to identify recurring patterns in auditors’ evaluations. The findings indicate that auditors who perceived strong managerial support, technological readiness, and a culture that values auditing reported positive perceptions, thereby reinforcing ICS effectiveness. Conversely, perceptions turned negative when auditors encountered structural inconsistencies, technological limitations, and inadequate responses to audit recommendations. The study concludes that ICS effectiveness in manufacturing is shaped not only by the technical robustness of control systems but also by the subjective experiences and perceptions of internal auditors. These insights provide a valuable basis for management to strengthen ICS design through enhanced independence, competence, and an audit-supportive organizational culture.